PERAN GURU PAI DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DI SMP MUHAMMADIYAH 16 BRONDONG LAMONGAN: PERAN GURU PAI DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DI SMP MUHAMMADIYAH 16 BRONDONG LAMONGAN - Yusuf Wibisono (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
Aqidah Akhlak is a person's inner state which is the source of the birth of actions. In increasing students' understanding of the subject of aqidah akhlak, infrastructure, learning tools, learning media, learning methods, and the role of educators at school and parents at home are needed. The purpose of this research is to describe the role of PAI teachers in improving students' understanding of Aqidah Akhlak subjects at SMP 16 Brondong Lamongan, describe Aqidah Akhlak learning at SMP Muhammadiyah 16 Brondong Lamongan, and describe the implementation of Aqidah Akhlak learning to students at SMP Muhammadiyah 16 Brondong Lamongan. This study uses a qualitative research approach by taking the object of SMP Muhammadiyah 16 Brondong Lamongan. Data collection is done by observation, interviews, documentation. Data analysis technique used are analysis before in the field and analysis while in the field. The results showed that the role of Islamic Religious Educations’ teachers in providing students' understanding of Aqidah Akhlak subjects are as follows: 1) The role of Islamic Religious Educations’ teachers in providing understanding to students on the subject of Aqidah Akhlak is to be a good role model (uswatun hasanah) both when with students and in the daily life of teachers, instilling the values ​​of aqidah and morals to students, being firm against deviations aqidah and morals to students and provide good advice to students. 2) Aqidah Akhlak in the teaching and learning process is divided into three sessions, opening, core activities, and closing, using lecture learning methods, telling stories, and linking learning materials with real things in everyday life. 3) Implementation of Aqidah Akhlak learning which is carried out in the form of getting used to activities at school in the form of praying Dhuha in congregation, praying for a sick teacher or friend, cultivating greetings, greeting smiles, and speaking good words to teachers.